RECOGNITION OF THE ARMENIAN GENOCIDE AS PART OF SOUTH CAUCASIAN AND MID-EASTERN POLITICS - MARTIROSIAN, Tigran (CENTRAL ASIA AND THE CAUCASUS, 2004)
Since restoring their country’s political independence, the Armenian leaders never tire of saying how important it is to have the world recognize the existence of the Armenian genocide and to redress the huge losses it has caused. This is set forth in the Declaration of Armenian Independence. In 1992-1997, certain political figures did a lot to push the issue beyond the range of attention; what is more, there was a lot of talk about the need to establish “close friendly” or, at least, “good-neighborly” relations with Turkey in order to allegedly ensure Armenia’s national independence. Later events demonstrated, how-ever, that Turkey took these statements for signs of weakness. Ankara failed to realize that international recognition of the 1915-1923 genocide was fraught with serious consequences and that it would be con fronted with huge problems in the sphere of international relations. This explains why Turkey intensified its embargo against Armenia under the pretext of needing to resolve the “Karabakh issue” in favor of Azerbaijan. The regime of then Armenian President Levon Ter-Petrossian was prepared to discuss the problem so as not to offend its western neighbor, which meant that the head of state was too frightened to discuss the possibility of international recognition of the Armenian genocide. The first president dismissed Foreign Minister Raffi Oganessian, who dared to mention the issue at an international conference in Istanbul.Zhirayr Liparityan,1 “éminence grise” of Armenia, repeatedly traveled to Turkey to assure its leaders of his continued dedication to Armenian-Turkish cooperation. More than that, the regime went as far as trying to prevent international recognition of the genocide. Amaiak Oganessian, who headed the Union of Political Scientists of Armenia, said that while discussing the international recognition issues in the State Duma of Russia he was pestered with phone calls from certain deputies of the Armenian parliament who demanded that he stop meddling in the issue.2